The Role of Informal Cooperation to Improve the Agricultural Practices: Case of El-Nafir in South Kordofan State, Sudan - Asma Elzubair; Amal A. Murad (Pusbindiklatren Bappenas, 2024)
El-Nafir is an informal cooperation form practiced in Sudan to accomplish various daily activities. Despite the important role of El-Nafir, especially in offering labours to farmers, no studies have been conducted to highlight its importance. Therefore, this study aimed to investigate the role of El-Nafir in improving agricultural practices in Abu Jubahyah Locality, South Kordofan State, Sudan. Heads of household (HHHs) questionnaires and field observations were used for primary data, where 75 HHHs were selected randomly. Descriptive analysis, T-test, and correlation analysis were performed using SPSS. The results showed that El-Nafir has contributed to improving agricultural production. The findings indicated that implementation per Fadden (4200 m²) is cost-effective and time-efficient. Implementing agricultural activities per Fadden via El-Nafir was low cost (18.01 US) compared to hired labourers (42.89 US). The study found that lack of financial support, shortage of skilled labours, lack of collective action awareness, war, and insecurity are the factors that influenced the success of El-Nafir's strategy. The study concluded that El-Nafir's strategy improved agricultural practices inside and outside the farms, including cultivation, crop harvesting, protection, and cleaning of the harvested crops. The study recommends the adoption of El-Nafir to enhance the agricultural production and marketing.